Evaluation on the Stability of Amine-Mesoporous Silica Adsorbents used for CO2 Capture - Dang, Viet Quang (H. : ĐHQGHN, 2020)
Amine-mesoporous silica has been considered as a promising CO2 adsorbent with high potential for the reduction of energy consumption and CO2 capture cost; however, its stability could greatly vary with synthetic method. In this study, adsorbents prepared by impregnating different amines including polyethylenimine (PEI) and 3-aminopropyltriethoxysilane (APTES) onto mesoporous silica were used to evaluate the effect of amines selection on the stability of adsorbents used in CO2 capture process. Results revealed that APTES impregnated mesoporous silica (APTESMPS) is more stable than PEI-impregnated mesoporous silica (PEI-MPS); APTES-MPS was thermally decomposed at ≈280 oC, while PEI-MPS was thermally decomposed at ≈180 oC only. PEIMPS was particularly less stable when operating under dry condition; its CO2 adsorption capacity reduced by 22.1% after 10 adsorption/regeneration cycles, however, the capacity can be significantly improved in humid condition. APTES-MPS showed a greater stability with no significant reduction in CO2 capture capacity after 10 adsorption/regeneration cycles. In general, APTES-MPS adsorbent possesses a higher stability compared to PEI-MPS thanks to the formation of chemical bonds between amino-functional groups and mesoporous silica substrate